Larry Ball’s The Fed and Lehman Brothers: A Review Essay - Chari, V. V. (Journal of Economic Literature, 2022)
Laurence Ball argues that the Federal Reserve (the Fed) could—and should—have bailed out Lehman Brothers so that it did not have to declare bankruptcy. He presents compelling evidence that it could have. I argue that the view that the Fed should not bail out Lehman is reasonable under the circumstances the Fed was in at the time. The Lehman bankruptcy is a case study in bailouts and the attendant moral hazard problem that expectations of bailouts create. The lessons learned imply a clear case for appropriate regulatory intervention to solve the problems created when governments cannot commit themselves to not undertake bailouts. (JEL D72, E32, E58, E63, G01, G24, G33)